Boys to men: Narrating life stories of fatherhood and work life amongst young black men - Langa, Malose (PINS-Psychology in Society, 2017)
This paper details the life stories of young black men, specifically how they negotiate their masculine identities over time. The researcher tracked a group of young black men over a period of nine years, from when they were adolescent boys (between the ages of 13 and 18 years), until they were young adults (between the ages of 23 to 26 years at the time of the writing). The aim of the study was to explore how the participants spoke about their relationships with their fathers as young adolescent boys and how they were now fathers to their own children as young men. At the beginning of the study, the participants were given disposable cameras and asked to take 27 photos (the total available on the film) under the theme, “My life as a young black man in the new South Africa”. The photos undertaken were used to facilitate semi-structured interviews in which the life stories of what it meant to be a young black man were shared. Between four to fourteen follow-up interviews were conducted with some of the participants. Key themes in the life stories included relationships with mothers, experiences of growing up without fathers, entering the world of work, and being fathers themselves which encouraged them to also reflect about their own relationships with their fathers. It is clear from their experiences that narratives of being a young black man are not static, but continuously change depending on the context, and time. In conclusion, it is argued that these positive voices of masculinities need to be promoted and celebrated.